The chemical and enzymatic hydrolysis of archaeological wood cellulose and monosaccharide purification by high pH anion exchange chromatography for compound-specific radiocarbon dating - Hodgins, G; Butters, T; Ramsey, C; Hedges, R (University of Arizona, 2001)
Preliminary experiments were carried out on archaeological wood to investigate methods of cellulose hydrolysis and carbohydrate monomer purification for the purpose of compound-specific radiocarbon dating. The Chelford log, a known 14C dead source of wood cellulose, was selected for study in order to investigate the levels of contamination introduced during sample purification. Two methods of hydrolysis were examined, mineral acid hydrolysis and enzyme hydrolysis using cellulase from Penicillium funiculosum. Under the conditions described, enzymolysis was far superior to acid hydrolysis in terms of the glucose monomer yield. Glucose monomer purification was accomplished using high pH anion exchange chromatography with pulsed amperometric detection. This high performance liquid chromatography (HPLC) method does not require sample derivatization and the chromatography products can be collected in water. These characteristics make it potentially well suited to carbon dating applications. 14C dating of chromatographically purified glucose fractions revealed significant levels of contamination had accumulated during both protocols. Glucose contamination from the cellulase enzyme preparation was a major source of contamination within the enzymatically hydrolyzed samples. Ultrafiltration of the enzyme removed some but not all of this contamination. The contamination must be reduced 10-fold before the methodology could be viable for dating. This hydrolysis/HPLC method is also being investigated for 14C dating of other carbohydrate polymers such as chitin. © 2001 by the Arizona Board of Regents on behalf of the University of Arizona.